PENGARUH PENAMBAHAN PATI SAGU (METROXYLON SAGO) TERHADAP STABILITAS DIMENSI BAHAN CETAK ALGINAT SEBAGAI BAHAN CETAK PADA PRAKTIK KEDOKTERAN GIGI - Gita Dwi Jiwanda Sovira; Lendrawati Lendrawati; Muhammad Taufik (Universitas Baiturrahmah, 2023)
Introduction: Impression material is a material used to obtain negative impressions of teeth and oral tissues. Alginate impressions have deficiencies in dimensional stability, thus affecting the accuracy of the impression. The imbibition and syneresis processes affect the dimensional stability of the alginate. To overcome the change in dimensional stability, modification of alginate with sago starch was carried out. Purpose: The aim of this study was to determine the effect of adding sago starch (Metroxylon sago) at concentrations of 32.5%, 37.5%, and 42.5% on the dimensional stability of alginate. Methods: In this study, a comparison of the dimensional stability of pure alginate and alginate-added sago starch will be observed. The method used was an experimental laboratory study with a pre-and post-test control group design. Results: The mean difference in the dimensional measurements of the two treatments in group A was 0.0110; group B was -0.0021; group C was -0.0006; and group D was -0.0016. Statistically, there was no significant difference (p>0.05) between filling for 0 minutes and 30 minutes in the alginate group with the addition of sago starch. Conclusion: There was a change in the dimensional stability of the gypsum impressions of pure alginate groups with the addition of 32.5%, 37.5%, and 42.5% sago starch. The alginate group, with the addition of 37.5% sago starch, experienced the smallest dimensional changes.